Statistical map analysis of the mean and the gini coefficient of healthcare expenses in Iran - Yadollah Waghei; Samaneh Nictinat; Gholam Reza Mohtashami Barzadaran (Gonabad University of Medical Sciences, 2015)
In many societies fairness and equality are the most significant concepts among the governments and peoples. In the health systems, the fast increase in expenses takes expert's attention to measure and control the inequality. The aim of this paper is to investigate the inequality of household's health expense's in the Iran and making its statistical map. The health expenses data for doing this research have been gotten from the statistical center of Iran (SCI). The process of preparing data and estimating the statistical indexes have been done using the S-PLUS software. Spatial analysis and predictions have been done by geoR. For making statistical maps we have used Arcgis9.2 software. We conclude that the mean of costs and its gini coefficient increases, from east to the west of Iran. The Gini coefficient of household's health expenses differs from 0.64 to 0.84, which show the existence of high inequality in this type of expenses. For eastern and north-western areas the least Gini coefficient had been predicted. In Sistan and Baluchestan and Hormozgan provinces the most inequality are predicted. Governments should try by financial aids decrease the inequality and receive fairness in health systems.